Co‐morbidity of depression, anxiety and fatigue in cancer patients receiving psychological care. Issue 4 (19th May 2016) - Zhu, Lei; Ranchor, Adelita V.; van der Lee, Marije; Garssen, Bert; Almansa, Josué; Sanderman, Robbert; Schroevers, Maya J.
Abstract: Objectives: This study aimed to examine (1) subgroups of cancer patients with distinct co‐morbidity patterns of depression, anxiety and fatigue; (2) how individuals transitioned between these patterns; and (3) whether socio‐demographic, clinical and psychological care characteristics distinguished patients' transitions. Method: This naturalistic, longitudinal study focused on 241 cancer patients receiving psycho‐oncological care in the Netherlands. Data were collected before initiation of psychological care (T1), 3 months (T2), and 9 months thereafter (T3). Latent transition analysis was performed examining research questions. Results: Three distinct co‐morbidity patterns were identified: class 1 ('mood disturbances and fatigue'), class 2 ('mood disturbances') and class 3 ('few symptoms of mood disturbances and fatigue'). Half of those in class 1 remained in this group from T1 to T3, a quarter transitioned to class 2 and another quarter to class 3. Baseline physical symptoms distinguished these transitions: those with more physical symptoms tended to remain stable. Half of patients in class 2 remained stable from T1 to T3, 46% moved into class 3 and 8% into class 1. Baseline physical symptoms and years after cancer diagnosis significantly distinguished these transitions: the 8% moving to class 1 had more physical symptoms and were longer after cancer diagnosis. Most patients in class 3 remained stable from T1 to T3, and predictors of transitions could not be examined. Conclusions: Three distinct co‐morbidity patterns of depression, anxiety and fatigue were identified and exhibited different symptom courses longitudinally. Those with poor physical health tended to report elevated mood disturbances and fatigue during psychological care. Copyright © 2016 John Wiley & Sons, Ltd.